Persepsi wanita menopause terhadap diri dan hubungannya dengan tingkat kecemasan - Zainap Tunrahmi; Syaiful Bahri; Abu Bakar (Jurnal Suloh, 2017)
Abstract: Physical changes, health and psychological disorders during menopause are reasons for the high level of anxiety of women. A woman who has a negative perception will have a high level of anxiety about menopause, and vice versa. This study raised the problem of self-perception, anxiety and the relationship of perceptions to the level of anxiety in women who experience menopause in Mukim Lam Ara, Darul Imarah District of Aceh Besar. The study population was 360 people. The study sample was taken using a proportionate stratified random sampling using the Slovin formula, so that a sample of 189 people was obtained. Data collection used a questionnaire method with a Likert scale model. Data analysis used descriptive statistical analysis and Product Moment correlation. The results showed that menopausal women generally had a positive self-perception and a low level of anxiety. It also found a negative relationship between the perception and anxiety level. In other words, it is evident that women who have a positive self-perception will have a low level of anxiety about menopause, and vice versa. Research still finds some women who worring the menopausal condition, even though with a minimal percentage; It is expected that the village government, community health center, and related parties in the local area will always strive to facilitate women and the community with various information and debriefing activities about menopause to minimize the development of negative perceptions in women, so as to reduce their anxiety level towards menopause. Thus a healthy society can be created, have a stable psychological development and far from excessive anxiety..Keywords: Perception, Menopause, Anxiety Level Abstrak: Perubahan fisik, gangguan kesehatan dan psikologis pada masa menopause menjadi alasan tingginya tingkat kecemasan para wanita. Wanita yang memiliki persepsi negatif akan memiliki tingkat kecemasan yang tinggi tentang menopause, demikian pula sebaliknya. Penelitian ini mengangkat masalah persepsi diri, tingkat kecemasan dan hubungan persepsi dengan tingkat kecemasan pada wanita yang mengalami menopause di Mukim Lam Ara Kecamatan Darul Imarah Kabupaten Aceh Besar. Populasi penelitian adalah 360 wanita, sampel diambil menggunakan proportionate stratified random sampling dengan rumus Slovin, sehingga diperoleh sampel sebanyak 189 orang. Pengumpulan data menggunakan metode kuesioner dengan model skala likert. Analisis data menggunakan analisis statistik deskriptif dan korelasi Product Moment. Hasil penelitian menunjukkan bahwa secara umum wanita menopause memiliki persepsi diri yang positif, tingkat kecemasan yang rendah, serta adanya hubungan yang negatif antara persepsi dan tingkat kecemasan. Dengan kata lain, terbukti bahwa wanita yang memiliki persepsi diri yang positif akan memiliki tingkat kecemasan yang rendah tentang menopause demikian pula sebaliknya.. Dengan masih ditemuinya beberapa wanita yang mencemaskan kondisi dirinya saat menopause, walau dengan persentase yang minim; diharapkan pada pemerintah desa, puskesmas, dan pihak-pihak terkait agar berupaya memfasilitasi para wanita dan masyarakat dengan berbagai informasi dan kegiatan pembekalan tentang menopause guna meminimalisir perkembangan persepsi negatif dalam diri para wanita, sehingga dapat mengurangi tingkat kecemasan terhadap menopause. Dengan demikian dapat tercipta masyarakat yang sehat, memiliki perkembangan psikologis yang stabil dan jauh dari rasa cemas berlebihan.Kata kunci: Persepsi, Menopause, Tingkat Kecemasan